Neuropsychiatric damage in Systemic Lupus Erythematosus: Possible protective role of medications. - Gonzáles-Naranjo, Luis A. (2013)
Objective: To examine the possible role of medications in the occurrence of neuropsychiatric damage in patientswith systemic lupus erythematosus (SLE). Material and methods: SLE patients from the LUMINA (Lupus inMinorities: Nature vs. Nurture) cohort (ACR criteria, ≥ 16 years of age at enrollment and ≤5 years of diseaseduration) were studied. Time-to-neuropsychiatric damage [defined according with the Systemic Lupus CollaboratingClinics (SLICC) Damage Index (SDI): neurocognitive impairment or psychosis, seizures, cranial or peripheralneuropathy, stroke or surgical resection not due to malignancies and transverse myelitis] was examined by univariableand multivariable Cox regression analyses. Propensity score analyses were done to further determine the possibleprotective role of hydroxychloroquine in neuropsychiatric damage occurrence. Results: Six-hundred and thirtytwopatients were studied. Age, Caucasian ethnicity, disease activity over time, diabetes and abnormal illness-relatedbehaviors were associated with a shorter time-to-the occurrence of neuropsychiatric damage whereas photosensitivity,anemia, Raynaud’s phenomenon, hydroxychloroquine and a medium dose of prednisone were associated with alonger time. Although the direction of the association remained the same by propensity score analyses(hydroxychloroquine), significance was no longer evident. Conclusions: Our data suggest a possible protectiverole of hydroxychloroquine and moderate doses of prednisone in the occurrence of neuropsychiatric damage inpatients with SLE. (Rev. Neuropsiquiatría 2008; 71: 51-57).